A Case study on the UP Integrated School Multi-Purpose Hall - Catura, Sheryl; Reyes, Maita; Kuizon, Edwin; Redoble, Cheryl (UP College of Engineering, 1991)
This case study endeavours to improve the services offered by the UP Integrated School Multi-Purpose Hall -Canteen,namely that of providing meals and snacks to the schools of 1,000 students and UPIS faculty.These services could be made more efficient if queuing at the meal counter and the chits counter can be eliminated. The kitchen layout was found to be in need of modifications. At present the work flow of the baker is blocked by the supervisor's desk and the oven and cooler are undesirably close. The layout was also the source of the long time spent in assembling a lunch plate.The above mentioned problems were solve by applying the techniques the authors have learned in Industrial Engineering such as facility layout and planning and methods study.The group,after careful evaluation is proposing a new,more efficient kitchen layout as well as a serving counter arrangement.A flow process is also recommended for the exchanging of cash to chits.The group also includes some areas for further investigation.